MiR-199a-5P promotes osteogenic differentiation of human stem cells from apical papilla via targeting IFIT2 in apical periodontitis - Hu, Jing; Huang, Xia; Zheng, Liwen; Zhang, Yuxin; Zeng, Huan; Nie, Li; Pang, Xiaoxiao; Zhang, Hongmei (Frontiers in Immunology, 2023)
Introduction Periapical alveolar bone loss is the common consequence of apical periodontitis (AP) caused by persistent local inflammation around the apical area. Human stem cells from apical papilla (hSCAPs) play a crucial role in the restoration of bone lesions during AP. Studies have recently identified the critical role of microRNAs (miRNAs) involved in AP pathogenesis, but little is known about their function and potential molecular mechanism, especially in the osteogenesis of hSCAPs during AP. Here, we investigated the role of clinical sample-based specific miRNAs in the osteogenesis of hSCAPs. Methods Differential expression of miRNAs were detected in the periapical tissues of normal and patients with AP via transcriptomic analysis, and the expression of miR-199a-5p was confirmed by qRT-PCR. Treatment of hSCAPs with miR-199a-5p mimics while loaded onto beta-tricalcium phosphate (β-TCP) ceramic particle scaffold to explore its effect on osteogenesis in vivo. RNA binding protein immunoprecipitation (RIP) and Luciferase reporter assay were conducted to identify the target gene of miR-199a-5p. Results The expression of miR-199a-5p was decreased in the periapical tissues of AP patients, and miR-199a-5p mimics markedly enhanced cell proliferation and osteogenic differentiation of hSCAPs, while miR-199a-5p antagomir dramatically attenuated hSCAPs osteogenesis. Moreover, we identified and confirmed Interferon Induced Protein with Tetratricopeptide Repeats 2 (IFIT2) as a specific target of miR-199a-5p, and silencing endogenous IFIT2 expression alleviated the inhibitory effect of miR-199a-5p antagomir on the osteogenic differentiation of hSCAPs. Furthermore, miR-199a-5p mimics transfected hSCAPs loaded onto beta-tricalcium phosphate (β-TCP) scaffolds induced robust subcutaneous ectopic bone formation in vivo. Discussion These results strengthen our understanding of predictors and facilitators of the key AP miRNAs (miR-199a-5p) in bone lesion repair under periapical inflammatory conditions. And the regulatory networks will be instrumental in exploring the underlying mechanisms of AP and lay the foundation for future regenerative medicine based on dental mesenchymal stem cells.